EVALUASI KINERJA JURU PUNGUT RETRIBUSI PELAYANAN PASAR DI UNIT PELAKSANA TEKNIS PASAR PADA DINAS PERDAGANGAN DAN PERINDUSTRIAN - Yoserizal, Bagas Ndaru Kartiko, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2020)
Evaluation of the Performance of Market Collector Levies in the Market Technical Implementation Unit at the Trade and Industry Office. This study aims to analyze the Evaluation of the Performance of Collectors Levies Market Services in the Market Technical Implementation Unit at the Department of Trade and Industry of the City of Pekanbaru and analyze the factors of obstacles and supporters that influence it. This study uses a descriptive qualitative research method approach. The research methods are interviews, observation, and study of literature. Data analysis uses descriptive qualitative methods. Research informants, namely: Head of Pekanbaru City Trade and Industry Office, Pekanbaru City Trade and Industry Office Market Head, Head of Levies Section, Head of Market Technical Services Unit, Market Levies and Market Traders. The results of this study indicate that an evaluation of the performance of market service levies collectors in the market technical implementation unit is needed to support the successful implementation of market service levies collection.